2007
DOI: 10.1128/jvi.01590-06
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of Type I Interferon Responses in Myeloid Dendritic Cells by Mosquito and Mammalian-Cell-Derived Alphaviruses

Abstract: Dendritic cells (DCs) are an important early target cell for many mosquito-borne viruses, and in many cases mosquito-cell-derived arboviruses more efficiently infect DCs than viruses derived from mammalian cells. However, whether mosquito-cell-derived viruses differ from mammalian-cell-derived viruses in their ability to induce antiviral responses in the infected dendritic cell has not been evaluated. In this report, alphaviruses, which are mosquito-borne viruses that cause diseases ranging from encephalitis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
116
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 46 publications
6
116
1
Order By: Relevance
“…Furthermore, the source of the virus may influence the induction of IFN. Thus, it has been reported that alphaviruses derived from mosquito cells induce less IFN than viruses derived from mammalian cells and that this might have an impact on the ability of the mosquito-borne virus to transfer to the vertebrate host (Shabman et al, 2007).…”
Section: Mode Of Action Virus Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the source of the virus may influence the induction of IFN. Thus, it has been reported that alphaviruses derived from mosquito cells induce less IFN than viruses derived from mammalian cells and that this might have an impact on the ability of the mosquito-borne virus to transfer to the vertebrate host (Shabman et al, 2007).…”
Section: Mode Of Action Virus Referencesmentioning
confidence: 99%
“…Furthermore, the source of the virus may influence the induction of IFN. Thus, it has been reported that alphaviruses derived from mosquito cells induce less IFN than viruses derived from mammalian cells and that this might have an impact on the ability of the mosquito-borne virus to transfer to the vertebrate host (Shabman et al, 2007).Clearly, in vivo, it would be expected that viruses would keep the production of viral PAMPs to a minimum. This may be achieved by having a replication strategy that minimizes the production of PAMPs by: (i) tightly controlling virus transcription and replication to minimize the production of PAMPs such as dsRNA [e.g.…”
mentioning
confidence: 99%
“…We chose Vero cells as a representative cell line to produce DENV as it is commonly used in vaccine studies to grow virus (reviewed by Whitehead et al, 2007). DENV produced in other mammalian cell types can also infect DC-SIGN-expressing U937 cells, including virus produced in human monocytic cells (data not shown).Previous studies with alphaviruses and WNV have demonstrated that mosquito cell-derived virus infects DC-SIGN-expressing cells better than mammalian cellderived virus (Davis et al, 2006b;Klimstra et al, 2003;Shabman et al, 2007). The superior infectivity of mosquito-derived virus was attributed to the presence of terminal high-mannose glycans in mosquito cell-but not in mammalian cell-derived virus.…”
mentioning
confidence: 99%
“…As DC-SIGN preferentially binds to terminal mannose residues, one would predict that viruses grown in insect cells would bind to this receptor and infect DCs better than viruses grown in mammalian cells. In fact, DC-SIGN can distinguish between mosquito-and mammalian cell-derived alphavirus E2 glycans, resulting in more efficient infection by mosquito cell-derived virus (Klimstra et al, 2003;Shabman et al, 2007Shabman et al, , 2008. Similarly, mosquito-derived West Nile virus (WNV), a flavivirus relative of DENV, also infects cells through DC-SIGN better than mammalian cellderived virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation